Interrelations of Myths and Motifs: A Socio-Cultural Viewpoint - Roopa Roshan Sahoo; Navaneeta Rath (Lakhomi Journal Scientific Journal of Culture, 2022)
Myths and motifs constitute the expressive and symbolic representation of the culture of a society. They are frequent in creative productions and relate to religion, philosophy, and society’s environment and social forces. Though independent studies on motifs and myths exist, studies describing their interrelationship are hard to discover. Further, their trajectory and interrelations are hardly discussed in social sciences and even in Sociology. Taking this dearth of knowledge into account, the present article tries to elaborate on these two concepts, chalk out their interpretations by Sociologists, and establish their interrelations. The article is based on secondary literature established through the content analysis method. The result and discussion are organized into four parts i.e. conceptual elaborations of motifs and myths, the Sociological knowledge production on motifs and myths, the interrelationship between myths and motifs, and the concluding lines. The study ends with the concluding lines that myths and motifs are cultural and social resources whose study needs to be brought out into the ambit of social science discourses.